Proses penyaluran maklumat dalam skop tadbir urus dasar pengurusan alam sekitar bandar - Ismail, Hamidi (College of Law, Government and International Studies, Universiti Utara Malaysia, 2012)
Information dissemination process from the government to the public within the scope of urban environmental policy governance is important because it affects awareness of the member of a community in maintaining the quality of urban environment.Good dissemination of information is needed, through certain channels, so that the community is able to manage the environment as envisaged by the policy. In the process of dissemination of information, there are two basic things namely effective information and communication.Both of these things need to be managed and carried out systematically so that the information received by the community can become evident and can be translated into action.However, issues related to noise in the dissemination of information should be avoided because it can reduce the quality of the information received by the community or reduce the effectiveness of the communication between the giver and receiver of information.This paper is of the view that good information flow is essential to the success of the policy or urban environmental governance.